The New Stage of Institutional and Legal Foundation of the EU Area of Freedom, Security and Justice - M. L. Entin; V. V. Voynikov; E. A. Torkunova (Московский журнал международного права)
Introduction. The area of freedom, security and justice (AFSJ) is one of the most dynamic areas of EU policy. The migration crisis, as well as the activation of terrorist organizations in the EU MS, had a significant impact on the Union's policy, which forced the EU to revise the EU AFSJ policy. At the moment we can identify the significant changes in the EU policy on AFSJ, which emphasize the particular relevance of this study.Materials and methods. This research is based on the scientific works of Russian and foreign researchers in the field of European integration and European law, as well as on the analysis of EU legal acts. The methodological basis of the research includes a variety of methods of scientific knowledge – philosophical, general scientific and special legal.Research results. The development of the legal component of the AFSJ is the result of the migration crisis and the increase in the terrorist threat, which had some "remedial" effect on the AFSJ. A common feature for all components of the AFSJ is the expansion the cooperation within Union and strengthening of the EU competence.Discussion and conclusions. There are two debated issues within this study. First, is there a risk of the collapse of the AFSJ, is there a danger that the EU will have to give up some of the achievements of the AFSJ? The authors of this article believe that, despite of current difficulties, the EU has a sufficient margin of safety in order to maintain and strengthen the main components of the AFSJ. Secondly, to what extent the EU experience in the field of AFSJ could be used within the framework of the Eurasian Economic Union (EAEU)? The development of the integration organizations shows that in the future the EAEU will face the need to harmonize migration and law enforcement policies. In this case the positive experience of the EU can be useful for the Eurasian integration.